The real impact of COVID-19 on community pharmacy professionals as part of the primary health care frontier workforce in Spain. - Marjan Manouchehri; Sukvinder K. Bhamra; María S. Fernández-Alfonso; Marta Gil-Ortega (GarVal Editorial Ltda., 2021)
Context: Spain was at the epicenter of the pandemic. Health centers across Spanish territory were not able to respond to non-emergency enquiries, leaving community pharmacies as the first point of patient's contact. Aims: To investigate the impact of COVID-19 on the mental and physical health of community pharmacy teams across Spain. Methods: A cross-sectional observational study was performed with community pharmacy professionals throughout Spain. A questionnaire designed by our collaborator from the United Kingdom was adapted to the Spanish population and launched between October 2020 and February 2021. Results: A total of 98 participants responded to the questionnaire. The survey showed an 80% increase in workload. The pandemic had negatively impacted the well-being of community pharmacy professionals. The survey indicated a national shortage of medicines and personal protective equipment across Spain, particularly during the first peak. To adapt to this pandora's box of COVID-19, 96% of the pharmacies changed their settings to improve patients and staff's safety. Most of these changes were self-financed by the pharmacy owner. The pharmacists kept up to date with information released from the pharmacists' college, General Pharmaceutical Council and the Spanish Society of Community Pharmacists. The Public domain purchased more (79%) immune booster supplements. Conclusions: Community pharmacy professionals have faced tremendous mental, physical and professional pressure in providing adequate personal protective equipment and medication supply to their communities. They have provided more pharmaceutical services during the crisis, although they have not been recognized as essential workers by the healthcare system.